Broadband optical frequency comb generator based on driving N-cascaded modulators by Gaussian-shaped waveform - Hmood, Jassim K.; Harun, Sulaiman Wadi (Elsevier, 2018)
A new approach for realizing a wideband optical frequency comb (OFC) generator based on driving cascaded modulators by a Gaussian-shaped waveform, is proposed and numerically demonstrated. The setup includes N-cascaded MZMs, a single Gaussian-shaped waveform generator, and N-1 electrical time delayer. The first MZM is driven directly by a Gaussian-shaped waveform, while delayed replicas of the Gaussian-shaped waveform drive the other MZMs. An analytical model that describes the proposed OFC generator is provided to study the effect of number and chirp factor of cascaded MZM as well as pulse width on output spectrum. Optical frequency combs at frequency spacing of 1 GHz are generated by applying Gaussian-shaped waveform at pulse widths ranging from 200 to 400 ps. Our results reveal that, the number of comb lines is inversely proportional to the pulse width and directly proportional to both number and chirp factor of cascaded MZMs. At pulse width of 200 ps and chirp factor of 4, 67 frequency lines can be measured at output spectrum of two-cascaded MZMs setup. Whereas, increasing the number of cascaded stages to 3, 4, and 5, the optical spectra counts 89, 109 and 123 frequency lines; respectively. When the delay time is optimized, 61 comb lines can be achieved with power fluctuations of less than 1 dB for five-cascaded MZMs setup.